Uneven economic overheating in a transforming party-state during the global crisis: The case of China - Mária Csanádi; Ferenc Gyuris (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
We scrutinize the systemic consequences of state intervention triggered by external shocks in the transforming Chinese economy before and after the global crisis. We interpret investment dynamics using a comparative party-state model concept framework. We identify the overinvestment as an outcome of the dynamics of party-state power formed by relations of dependence and interest promotion between party, state and economic decision-makers and of emerging structural motivations inside of this network. Due to the structural and operational characteristics of the party-state network, which are self-similar in time, space and at various aggregation levels, overinvestment and economic overheating can also be detected on the provincial level. This local phenomena is intensified by the specific decentralized pattern of power distribution of the Chinese party-state system. Thus, local intensity of overheating is further increased by major state interventions reacting to external shocks. Overheating is further amplified during economic transformation by market actors adapting to network priorities. Investment swings in both heating and cooling periods hide different forms of behavior in enterprises with different ownership types.
Keywords: O53; P12; P16; P2; P26; P31; 330; China; crisis; overheating; overinvestment; party-state; system transformation; enterprise behaviour